Study on Interaction Between Cefixime and Bovine Serum Albumin by Modified Fluorescence Spectroscopy - Zhang, Lihui; Liu, Baosheng; Li, Zhiyun; Guo, Ying (Asian Journal of Chemistry, 2015)
The reaction mechanism between cefixime (CFX) and bovine serum albumin (BSA) at different temperature was investigated by the classical fluorescence spectroscopy with focus on the fluorescence change of protein, as well as the elastic scattering fluorescence spectroscopy with focus on the fluorescence change of drug. The results indicated that cefixime could quench the intrinsic fluorescence of bovine serum albumin strongly through a static quenching process. The electrostatic force played an important role on the conjugation reaction between cefixime and bovine serum albumin, the number of binding site (n) in the binary system was approximately equal to 1. The binding constant obtained from elastic scattering fluorescence spectroscopy was larger than the one obtained from classical fluorescence spectroscopy by two orders of magnitude for the CFX-BSA system. At last the correctness of elastic scattering fluorescence spectroscopy method was verified by UV-visible absorption spectroscopy. It is also speculated that "point to side" interaction between drugs and peptides was existed.